Content Mastery Service : A Help In Related Consulting Problems Student Learning Activities - Metha Eka Juniyarti; Prayitno Prayitno; Marjohan Marjohan (International Journal of Research in Counseling and Education, 2018)
Learning activities can occur everywhere, including in the school environment. Learning activities in schools have various components that enable the emergence of student learning problems. These problems affect or even determine the quality of student learning outcomes. The Role of Guidance and Counseling, among them in the form of Content Mastery Services is needed to overcome these problems. This role becomes the main task of school counselors to optimize student learning outcomes. This article is a literature review. The results of the study show the discussion on the important role of Content Mastery Service on the quality of student learning activities in schools.